URGENSI NASIONALISME DALAM PENDIDIKAN MULTIKULTURAL - Tri Utomo, Sigit; Syakur, Achmad (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2022)
Indonesian nationalism cannot be separated from the fact that Indonesia is a plural and multicultural society with its cultural diversity and complexity. Indonesia is a plural country, both in terms of ethnicity, race, religion, and belief. This diversity in Indonesia raises several problems, such as inter-ethnic fights, separatism, and the loss of humanity to respect the rights of others. To solve this problem, a solution is needed, one of which is a multicultural education model. Multicultural education is expected to be able to answer the challenges of today's era. The application of multicultural education in Indonesia is still experiencing various obstacles or problems. One of the problems of multicultural education in Indonesia is the lack of community nationalism which causes a lack of tolerance for other people with different cultures and cultures. Indonesia's cultural diversity requires a force that unites the entire plurality of the country. Pancasila as the nation's view of life, national personality and state ideology functions.Keywords: Urgency, Nationalism, Multiculturalism